High MICs for Vancomycin and Daptomycin and Complicated Catheter-Related Bloodstream Infections with Methicillin-Sensitive Staphylococcus aureus - San-Juan, Rafael (Emerg Infect Dis, 2016)
We investigated the prognostic role of high MICs for antistaphylococcal agents in patients with methicillin-sensitive Staphylococcus aureus catheter-related bloodstream infection (MSSA CRBSI). We prospectively reviewed 83 episodes from 5 centers in Spain during April 2011–June 2014 that had optimized clinical management and analyzed the relationship between E-test MICs for vancomycin, daptomycin, oxacillin, and linezolid and development of complicated bacteremia by using multivariate analysis. Complicated MSSA CRBSI occurred in 26 (31.3%) patients; MICs for vancomycin and daptomycin were higher in these patients (optimal cutoff values for predictive accuracy = 1.5 μg/mL and 0.5 μg/mL). High MICs for vancomycin (hazard ratio 2.4, 95% CI 1.2–5.5) and daptomycin (hazard ratio 2.4, 95% CI 1.1–5.9) were independent risk factors for development of complicated MSSA CRBSI. Our data suggest that patients with MSSA CRBSI caused by strains that have high MICs for vancomycin or daptomycin are at increased risk for complications.